Analysis of the Metaphors in the Song ‘All Too Well’ by Taylor Swift as a Tool for Storytelling - Ela Sofiarti Sofian; F. X. Sawardi (Jurnal Lingua Idea, 2022)
Language is used by humans to communicate and express their ideas as well as feelings, which can be done through literary works such as a song. A song conveys an idea and/or a feeling through its lyrics. In a song, the lyrics may contain various metaphors that carry contextual meaning in order to convey a feeling and emotion. Thus, people may have different interpretation of a song. This applies to all kinds of songs, such as the longer version of Taylor Swift's song, "All Too Well". Therefore, this research will discuss 1) the meaning of the metaphors in the song to help create a better storytelling and 2) the type of metaphors used in the song. The metaphors found in this song will be analysed using Ullman’s theory on metaphors. The method used in this research is descriptive qualitative method because this research will describe the results of this research instead of depict them through numbers. The data in this research is the metaphors found in the song, and the sampling technique for this data is purposive sampling. This technique is chosen because this technique help supplies the data needed to answer the problems of this research. In relations to the aims of this research, there are 26 metaphors found to be used in this song; 3 anthropomorphic metaphors, 1 animal metaphor, 19 concrete to abstract metaphors, and 3 synesthetic metaphors. The use of these metaphors is intended not only so the story in the song can be better delivered to the listeners to make it more captivating, but also for the listeners to be able to understand the depths of emotions the song-writer wished to convey in the song. Therefore, the metaphors have significant influences in the act of storytelling through the lyrics of the song.